The effect of social representations of citizenship on establishing voluntary work for a university students: -A field study on a sample of Algerian universities students- - Bensouilah, Lilia (Journal of Human Sciences, 2021)
This study aims to identify the impact relationship between social representations of citizenship and the culture of volunteering among university students. To do this, we developed 250 electronic questionnaires which were distributed via the Messenger application. We performed statistical analysis of the data using the SPSS program. The results confirmed that students are moving towards paradigms which tend to structure voluntary practices linked to environmental activities and charitable work which does not accept any submission for political purposes. By emphasizing the primordial role of the religious system in shaping social representations which emphasize the importance of volunteering and give it a social legitimacy which connotes a positive appreciation.